Symbiotic Associations in the Phenotypically-Diverse Brown Alga Saccharina japonica - Balakirev, Evgeniy S.; Krupnova, Tatiana N.; Ayala, Francisco J. (PLOS ONE, 2012)
The brown alga Saccharina japonica (Areschoug) Lane, Mayes, Druehl et Saunders is a highly polymorphic representative of the family Laminariaceae, inhabiting the northwest Pacific region. We have obtained 16S rRNA sequence data in symbiont microorganisms of the typical form (TYP) of S. japonica and its common morphological varieties, known as “longipes” (LON) and “shallow-water” (SHA), which show contrasting bathymetric distribution and sharp morphological, life history traits, and ecological differences. Phylogenetic analysis of the 16S rRNA sequences shows that the microbial communities are significantly different in the three forms studied and consist of mosaic sets of common and form-specific bacterial lineages. The divergence in bacterial composition is substantial between the TYP and LON forms in spite of their high genetic similarity. The symbiont distribution in the S. japonica forms and in three other laminarialean species is not related to the depth or locality of the algae settlements. Combined with our previous results on symbiont associations in sea urchins and taking into account the highly specific character of bacteria-algae associations, we propose that the TYP and LON forms may represent incipient species passing through initial steps of reproductive isolation. We suggest that phenotype differences between genetically similar forms may be caused by host-symbiont interactions that may be a general feature of evolution in algae and other eukaryote organisms. Bacterial symbionts could serve as sensitive markers to distinguish genetically similar algae forms and also as possible growth-promoting inductors to increase algae productivity.